What are the risks associated with hormone therapy in transgender patients?. Issue 5 (May 2017) - Wenger, Hannah; Egan, Mari
Abstract : EVIDENCE‐BASED ANSWER : All‐cause mortality is higher in male‐to‐female (MtF) transgender patients on hormone therapy than untreated males. It is unclear if this difference is due to the hormonal therapy or other factors (HIV/AIDS, illicit drug use, suicide). Hormone therapy for MtF patients is associated with an increased risk of thromboembolic disease, cholelithiasis, hyperprolactinemia, transaminitis, and triglyceride elevations. Masculinizing hormones in female‐to‐male (FtM) transgender patients are not associated with increased mortality, myocardial infarction (MI), hypertension, or venous thromboembolism (VTE), but are associated with minimal changes in high‐density lipoprotein (HDL) cholesterol and systolic blood pressure (BP) (SOR: B, 2 cohort studies and meta‐analysis of cohort studies).